Empire in retreat : the past, present, and future of the United States - Bulmer-Thomas, V. (Yale University Press, 2018)
A sweeping history of the United States through the lens of empire-and an incisive look forward as the nation retreats from the global stage A respected authority on international relations and foreign policy, Victor Bulmer†'Thomas offers a grand survey of the United States as an empire. From its territorial expansion after independence, through hegemonic rule following World War II, to the nation's current imperial retreat, the United States has had an uneasy relationship with the idea of itself as an empire. In this book Bulmer†'Thomas offers three definitions of empire-territorial, informal, and institutional-that help to explain the nation's past and forecast a future in which the United States will cease to play an imperial role. Arguing that the move toward diminished geopolitical dominance reflects the aspirations of most U.S. citizens, he asserts that imperial retreat does not necessarily mean national decline and may ultimately strengthen the nation†'state. At this pivotal juncture in American history, Bulmer†'Thomas's uniquely global perspective will be widely read and discussed across a range of fields.